Design and manufacturing of a potato sorting machine for the blanca Yungay variety in the Junin region-Peru - Garcia Gonzales, Yahir Piero (2025)
ABSTRACT — This project is aimed at the agricultural sector, especially small and medium - sized tuber traders. Worldwide Peru ranks as the fourteenth producer of the Andean tuber, where potato production is the highest contributor to the economy of the agricultural sector due to the intense activity of about 330 thousand hectares of cultivation, distributed in 19 regions having the Junín Region as one of the largest contributors in the production of this tuber. For the marketing of the potato the most important part is its classification. That's why it has to be catalogued according to its dimensional and quality characteristics to establish a certain price for the product. That's why we designed a machine that performs the function of sorting by size in a much shorter time to minimize the labor employed. The prototype was designed through the fulfillment of a list of requirements and structure of functions divided within a morphological matrix in order to find various solution concepts, which were evaluated technically and economically for the ideal choice of the final prototype. The design was carried out through simulations carried out with the SolidWorks Simulation CAD software and through mathematical calculations, it was possible to obtain a machine that classifies 50 kg of potato in an interval of 1 to 2 min. The prototype has manual operation through a crank - crank connecting rod system, it also has as an option the installation of an internal combustion engine for the operation of the sorting screen.